GAMBARAN RESILIENSI IBU YANG MEMILIKI ANAK TUNADAKSA SEJAK LAHIR (Studi di Kelurahan Sendangmulyo Kecamatan Tembalang Kota Semarang) - Nita Anggraini; Besar Tirto Husodo; Syamsulhuda Budi Musthofa (Jurnal Kesehatan Masyarakat (Undip), 2017)
In Indonesia there are 32.990 children of whom are disabilities. In Semarang city until march 2017 there are 1.217 people with special needs. Tembalang district has the highest number of children with special needs, it is 277, 95 of which are found in sendangmulyo. Mothers who have children with physical disabilites are still unable to accept the presence of a child who hasphysical disabilities so that it affects the development and growth of a child who has physical disabilities. Mothers should be able to become a resilient individual with the condition of his son who was born with physical disabilities.The purpose of this study is to understand the description of mothers resiliencewho have children with physical disabilities since birth. The type of this research is qualitative descriptive research, data collection is by in-depth interview to 6 respondents with purposive sampling method. Processing and data analyses is validity and reliability by source triangulation to 5 people.The results showed that one respondent was still on the succumbing stage, this stage is the lowest stage of resilience. Respondents at this stage handed over all of child care to domestic servants, respondents did not intervene in the care of the child they were born with. The other three respondents are in the survival stage, respondents are able to care for their children even with the help or service of others. Two other respondents are in the recovery phase, respondents are able to accept the fact that their child was born with physical disabilities and since birth the respondent takes care of his or her own child without the help of others. In addition, the respondents were able to provide social support to the child with physical disabilities. Based on research suggested mother able to increase self-efficacy so that mother able to be in the recovery phase, so that mother able to accept and take care of children with physical disabilities since birth.